European Projects: a Pending Subject for Educational Inspection - Villarán Adánez, Alfonso (Avances en Supervisión Educativa, 2024)
European projects constitute a way of approaching the European educational space. Numerous schools, teachers and students regularly participate in them each year, which contributes to opening horizons and creating multinational and multicultural ties, in addition to exchanging experiences and learning about working methods. The Spanish educational inspectorate has traditionally been far from these projects, although every day there are more inspector interested in them and different initiatives and participations have already emerged, even as organizing partners. The importance of the inspectorate’s participation in these programs is related to its supervisory and advisory function in schools, which, for now, have a great advantage in this area. Despite the difficulties that arise for the implementation of initiatives by inspectors (especially bureaucratic and language ones), the advantages offered by these projects and the applications in the daily woks of inspectors advise greater involvement and participation in them, as they allow us to learn about other realities, share ideas and promote teamwork.